Acting as Expected: Global Leadership Preferences and the Pursuit of an Integrated Supply Chain. Issue 3 (5th August 2019) - Kull, Thomas; Wiengarten, Frank; Power, Damien; Shah, Piyush
Abstract : While research has extensively explored the potential benefits companies gain with integrated supply chains, the topic of why some companies are better at pursuing supply chain integration (SCI) is relatively under‐examined. We take the perspective that SCI is associated with preferred forms of leadership using leadership preference derived from path–goal logic. By combining global data sources, we examine the relationships among leadership style preferences, internal integration (i.e., between sales and purchasing) programs, and external integration (i.e., supplier side) programs. Our country‐level results challenge the assumption that the choice to pursue internal and external integration has similar origins. Specifically, while collaborative‐style leadership preferences relate to internal integration programs, societies preferring individualistic‐style leaders will be predisposed toward external integration programs. Our study's contribution is in the novel use of theories on leadership to explain variations in approaches toward supply chain integration.